Cultivation of Industrial Fibre Hemp (Cannabis sativa L.) in Iceland. How can we produce high-quality long fibre for use in textile applications? - Bethina Elverdam Nielsen 1982- (2022)
Though hemp possesses high-quality fibres that are valuable for the production of fine-quality yarns, and signs of hemp cultivation have been traced to about 8,000 years ago, long hemp fibres are not yet commercially manufactured into fine, thin yarns. But a renewed interest in this newly legal plant has arisen for industrial purposes in numerous fields. Many researchers and businesses are looking into how it could be used as a raw material and as a green solution. This thesis investigated the potential of cultivating Cannabis sativa in Iceland for long fibre yield and how it should be processed to produce quality fibres for textile applications. A qualitative investigation was conducted as traditional desk research, where efforts were made to give an overview of the process and involvement in the cultivation of industrial fibre hemp with a focus on long fibre yield. Relevant data were collected and analysed to gain a broader understanding of the subject and more insight into the research. A systematic literature review was then conducted, emphasising the long fibre yield of hemp cultivation in northern latitudes, which was compared and interpreted in the discussion chapter. Afterwards, other reports were brought in to go more in-depth on processing long hemp fibre for textiles in Scandinavia and Iceland. This methodology was chosen due to the novelty of the subject and because almost no research has been done on the topic in Iceland. This thesis concludes that cultivating hemp for long fibre in Iceland is possible, especially with a careful selection of cultivars. However, difficulties still need to be addressed in the production process. Much research is needed in cultivar testing and finding the proper retting process, which has proven to be the biggest obstacle.